SYNTHESIS AND BIOLOGICAL EVALUATION OF SOME NEW HYDRAZONE DERIVATIVES BEARING PYRIMIDINE RING AS ANALGESIC AND ANTI-INFLAMMATORY AGENTS - KAYMAKÇIOĞLU, BEDİA; TOK, FATİH; ARICIOĞLU, FEYZA (POLSKIE TOWARZYSTWO FARMACEUTYCZNE, 2018)
New hydrazone derivatives were synthesized from 4-chloro-2-(methylthio) pyrimidine-5-carbohydrazide. IR, 1H-NMR, 13C-NMR, mass spectral data and elemental analysis characterized synthesized compounds. All compounds were investigated for analgesic and anti-inflammatory activity with hot plate test and biochemical assay, respectively. The results of anti-inflammatory activity showed that compound 2t had maximal lipoxygenase (LOX) inhibition (66.30%) whereas inhibitions of 2a, 2c, 2i, 2k, 2l, 2m, 2p, 2s, and 2u were observed between approximately 45-15%. Our results also indicated that 15 compounds of 21 had an analgesic effect in hot plate test. Analgesic effect of 2l, 2s, 2t began earlier than others while the effect of 2i began at the latest time. According to the activity results, compound 2t have both significant analgesic and anti-inflammatory effects.
Keywords: Hydrazones; analgesic activity; anti-inflammatory activity; ANTIFUNGAL ACTIVITY; DESIGN; ANTIOXIDANT; INHIBITION